EVALUATION OF COMMUNITY SATISFACTION LEVEL ON THE QUALITY OF VILLAGE ROAD INFRASTRUCTURE DEVELOPMENT IN THE VILLAGE FUND PROGRAM - Bobby Fandra; Mona Foralisa Toyfur; Hanafiah Hanafiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
The development of road infrastructure is one of the determinants of the success of the development of an area. Good roads have a very important role to support community activities such as clothing, food, education and health. The purpose of this study is to analyze how much physical quality is in the implementation of road infrastructure development in the Sugih Waras, Muara Telang and Kuripan villages, Teluk Gelam District through the Village Fund Program. This research uses literature study research methods, while data collection is done by exploring information related to the problems to be discussed through scientific papers, books, journals and the internet. The results showed that all variables showed the results of the F test with a significance of 0.000 and the correlation value of the data exceeded the table correlation value, the test variable could be declared valid with the value of the questionnaire community data processing being 0.088 while the correlation value from the table of the results of the questionnaire processing device was 0.297. So it can be said that Location (X1), Labor (X2) and Building Quality (X3) have a significant effect on community satisfaction.